Fabrication of copper decorated tungsten oxide–titanium oxide nanotubes by photochemical deposition technique and their photocatalytic application under visible light - Momeni, Mohamad Mohsen (Applied surface science, 2015)
Schematic presentation of the pretreatment method of titanium sheets and producing process of WTNs and Cu/WTNs films on titanium foils. •WO3–TiO2 nanotubes (WTNs) were synthesized by one-step electrochemical anodizing.•Copper decorated WO3–TiO2 nanotubes (Cu/WTNs) were successfully prepared by photochemical deposition.•Photocatalytic activity of Cu/WTNs is higher than that of bare WTNs.•These photocatalysts showed good stability and it could be recycled several times without significant loss of its activity. Copper decorated WO3–TiO2 nanotubes (Cu/WTNs) with a high photocatalytic activity were prepared by anodizing and photochemical deposition. Highly ordered WO3–TiO2 nanotubes (WTNs) on pure titanium foils were successfully fabricated by electrochemical anodizing and copper deposited on these nanotubes (Cu/WTNs) by photoreduction method. The resulting samples were characterized by various methods. Only the anatase phase was detected by X-ray diffraction analysis. The presence of copper in the structure of thin films was confirmed by energy dispersive X-ray spectrometry and X-ray diffraction. The extension of optical absorption into the visible region of as-prepared films was indicated by UV/Vis spectroscopy. The degradation of methylene blue was used as a model reaction to evaluate the photocatalytic activity of the obtained samples. Results showed that the photocatalytic activity of Cu/WTNs samples is higher than bare WTNs sample. Kinetic research showed that the reaction rate constant of Cu/WTNs is approximately 2.5 times higher than the apparent reaction rate constant of bare WTNs. These results not only offer an economical method for constructing Cu/WTNs photocatalysts, but also shed new insight on the rational design of a low cost and high-efficiency photocatalyst for environmental remediation.